Soil phosphorus and disturbance influence liana communities in a subtropical montane forest - Malizia, Agustina (2010)
Questions: What are the effects of soil, topography, treefall gaps, tree species composition, and tree density on liana species composition and total liana abundance? Location: A 6-ha permanent plot in a subtropical montane forest in northwest Argentina. Methods: Multiple regressions were used to quantify associations of liana species composition and total liana abundance with edaphic, disturbance and tree community variables. Gradients in liana and tree species composition were quantified using principal components analysis (PCA). Results: Liana species composition was correlated most strongly with soil phosphorus concentration (R2=0.55). Total liana aanased with phosphorus and the density of recent treefall gaps (R2=0.60). Conclusions: In our study area, liana composition and abundance are most strongly correlated with features of the physical environment, rather than host tree characteristics. Our results support the hypothesis that recent increases in liana abundance in mature tropical forests may be related to increased rates of gap formation.